2020
DOI: 10.1016/j.asmr.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Suture-Button Versus Hook-Plate Fixation for Acromioclavicular Joint Injuries—A Systematic Review of Comparative Studies

Abstract: Purpose To systematically review the comparative studies in the literature to compare joint stability, clinical outcomes, and complications of acromioclavicular joint fixation using a hook plate versus arthroscopic suture-button (SB) fixation. Methods A literature search was performed in accordance with the PRISMA guidelines to identify clinical studies comparing the hook plate and arthroscopic SB techniques for acromioclavicular joint injuries. Qualitative statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In light of a considerable rate of concomitant intra-articular injuries, the arthroscopic technique provides the distinctive advantage of diagnosis and treatment of these pathologies. In contrast, an open approach and open reduction and internal fixation using a hook plate has long been considered the gold standard in ACJ reconstruction, but recent studies have shown the superiority of minimally invasive techniques, which is in line with the recent literature about the dynamic nature of the ACJ [ 17 22 ].…”
Section: Discussionmentioning
confidence: 59%
“…In light of a considerable rate of concomitant intra-articular injuries, the arthroscopic technique provides the distinctive advantage of diagnosis and treatment of these pathologies. In contrast, an open approach and open reduction and internal fixation using a hook plate has long been considered the gold standard in ACJ reconstruction, but recent studies have shown the superiority of minimally invasive techniques, which is in line with the recent literature about the dynamic nature of the ACJ [ 17 22 ].…”
Section: Discussionmentioning
confidence: 59%
“…While—accounting for the high ICC values of the measurements — the increased CCD of 2.0 ± 1.9 mm after hardware removal, which is 20-fold larger that applied measurement accuracy of 0.1 mm, is quantifiable, it seems to be marginal when compared to hardware removal after hook plate fixation. CCD increases between 3 and 13 mm [ 11 , 18 , 25 ] and a loss of reduction of more than 2 mm have been reported in 68% of the patients [ 19 ] following hardware removal after hook plate fixation. Acknowledging that a substantial loss of reduction was rare (< 5%), removal of the suspensory fixation system does not categorically jeopardize the postoperative result of AC joint stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Within this technical approach, adequate intraoperative coracoclavicular (CC) reduction is the cornerstone of a successful treatment ensuring long-term stability [ 17 , 22 , 26 , 29 , 33 ]. While advantages of high-tensile suture tape suspensory techniques include minimal invasiveness without the necessity of hardware removal [ 5 , 25 , 40 ], in rare cases, removal of hardware may be indicated due to mechanical irritation, local pain, or cosmetical reasons. With a high incidence of considerable loss of correction being reported following hardware removal after open AC stabilization using hook plates [ 18 , 32 , 40 ], there is a paucity of evidence investigating the incidence of loss of reduction following hardware removal after arthroscopically assisted stabilization of AC joint separation using high-tensile suture tape suspensory fixation systems.…”
Section: Introductionmentioning
confidence: 99%
“…The most crucial advantage of the TR method is that there is no need for a second operation to remove the implant. Some studies reported better results with the TR technique than the HP technique 16 , 17 . Lloyd et al 17 conducted a systematic review including 6 clinical studies with 285 patients and reported that the suture-button (including TR) technique resulted in higher CMSs and lower VAS scores.…”
Section: Discussionmentioning
confidence: 99%
“…According to a newly published meta-analysis by Lloyd et al 17 , the TR technique resulted in better functional outcomes and a reduced Visual Analog Scale (VAS) pain score than the HP technique, whereas other studies did not come to this conclusion 18 , 19 . The present study aimed to compare the clinical and radiological results of a minimally invasive CC fixation with an STR (MITR) technique and the HP technique for acute AC joint dislocation treatment.…”
Section: Introductionmentioning
confidence: 99%